1978
DOI: 10.1038/bjc.1978.221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lymphocyte supernatants on the electrophoretic mobility of erythrocytes: significance in cancer diagnosis

Abstract: Summary.-We have determined that when an extract of human brain is preincubated with lymphocytes its subsequent capacity to inhibit the electrophoretic mobility of tanned and stabilized erythrocytes is much reduced. There is a differential effect, however, as the observed reduction is from 73% inhibition to 35% when the pre-incubation is with lymphocytes from patients with malignant disease, but from 73% to 10% when it is with lymphocytes from normal controls. These values were obtained at a brain extract conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Several centres (using EF, CaBP or the KCI extracts as "antigens") confirmed the results of MEM (Pritchard et al, 1972(Pritchard et al, , 1973Preece & Light, 1974;Field, 1976;Irmscher et al, 1975;Klausch et al, 1975;Meyer-Rienecker et al, 1975;Jenssen et al, 1976a,b;Nowak et al, 1976;Klausch et al, 1977;Light & Preece, 1977;Muller et al, 1977;Gunther et al, 1978), MOD-MEM (Pritchard et al, 1976) and EMT (Jenssen & Shenton, 1975;Lampert et al, 1977;Shenton et al, 1977;Douwes et al, 1978;Dyson & Corbett, 1978;Tautz et al, 1978;Ritter & Oehme, 1978;Kreienberg et al, 1979;B6gelspacher et al, 1980), though the procedures have not gained universal recognition (see also Bagshawe, 1973;leading article in Nature, 1973;editorial in Lancet, 1976;Bagshawe, 1977;Moore & Lajtha, 1977;Moore, 1978).…”
mentioning
confidence: 58%
“…Several centres (using EF, CaBP or the KCI extracts as "antigens") confirmed the results of MEM (Pritchard et al, 1972(Pritchard et al, , 1973Preece & Light, 1974;Field, 1976;Irmscher et al, 1975;Klausch et al, 1975;Meyer-Rienecker et al, 1975;Jenssen et al, 1976a,b;Nowak et al, 1976;Klausch et al, 1977;Light & Preece, 1977;Muller et al, 1977;Gunther et al, 1978), MOD-MEM (Pritchard et al, 1976) and EMT (Jenssen & Shenton, 1975;Lampert et al, 1977;Shenton et al, 1977;Douwes et al, 1978;Dyson & Corbett, 1978;Tautz et al, 1978;Ritter & Oehme, 1978;Kreienberg et al, 1979;B6gelspacher et al, 1980), though the procedures have not gained universal recognition (see also Bagshawe, 1973;leading article in Nature, 1973;editorial in Lancet, 1976;Bagshawe, 1977;Moore & Lajtha, 1977;Moore, 1978).…”
mentioning
confidence: 58%
“…The collection of blood samples and isolation of lymphocytes (Dyson & Corbett, 1978) was unchanged, with the exception that Lymphocyte Separation Medium (Flow Laboratories, Irvine, Ayrshire) replaced Ficoll-Paque for the latter part of the investigation. No difference in lymphocyte recovery, or in results, were observed when the 2 media were compared.…”
Section: Methodsmentioning
confidence: 99%
“…We were able to reproduce their results and, in an initial trial, found the test system to detect the presence of malignancy with a success rate of some 80% (Dyson & Corbett, 1978). However, we differed from Porzsolt et al (1975) who reported their test system as a modification of the MEM test, which is generally accepted as having an immunological basis (Dickinson, 1979), in considering the test using tanned erythrocytes to be nonimmunological, and depending on the alteration of a physiological factor in the presence of malignancy (Dyson & Corbett, 1978).…”
mentioning
confidence: 90%
See 2 more Smart Citations